DETERMINANTS OF RICE CONSUMPTION AND HOUSEHOLD PREFERENCES IN JOS-NORTH, PLATEAU STATE, NIGERIA - Godfrey Onuwa; Alexander Dalla (Socio-Economics/Agribusiness Department, 2023)
The determinants of rice consumption and household preferences were analyzed. Multistage sampling was adopted and primary data analysed using descriptive statistics and OLS regression model. Socioeconomic factors affected rice consumption and household preferences. Local rice consumption was prevalent. Variables in the regression model were significant determinants of household's rice consumption. Constraints identified also affected rice consumption in the area. Price regulation, technology adoption, and policy modifications are strongly recommended.